Australian Primary School Students' Knowledge of the Agricultural Industry - Amy Cosby; Eloise S. Fogarty; Jaime Manning (MDPI AG, 2023)
The teaching of agriculture is critical to ensure students understand where their food and fibre originate, as well as the industry's contribution to the economy. This research examines the agricultural knowledge of Australian primary school students. Grade 4-6 students (n = 2392) from 75 schools were surveyed in 2021. The students' mean knowledge score was 8.7 out of 13 (SD = 2.1). The students exhibited a reasonable understanding of animal-derived products compared to plant-derived products, particularly when the plant product has undergone substantial processing. However, the students lacked an understanding of modern animal production systems, including the use of technologies on farms. This research identifies the gap in students' agricultural knowledge and provides insight to the industry to design and implement programs to improve their understanding.